Inferring potential non-disclosed men who have sex with men among self-reported heterosexual men with HIV in Southwest China: A genetic network study. - Yi Chen; Guanghua Lan; Yi Feng; Yuhua Ruan; Zhiyong Shen; Edward B McNeil; Kailing Tang; Jinghua Huang; Yiming Shao; Mei Lin; Virasakdi Chongsuvivatwong (PLoS ONE, 2023)
Background In Guangxi province of China, there is a high prevalence of HIV in the general population and in men who have sex with men (MSM). However, there is still a low proportion of MSM among people living with HIV. This apparent contradiction could be due to the high proportion of potential non-disclosed MSM (pnMSM) among reported heterosexual men. We analyzed the genetic linkage of HIV specimens to address this problem aiming to (1) identify the optimal genetic distance threshold, which gave the highest number of genetic clusters, (2) document the proportion of potential non-disclosed MSM (pnMSM) among self-reported heterosexual men, and (3) determine predictors for pnMSM. Methods Pairwise genetic distances were computed among all samples. The genetic distance threshold giving the highest number of genetic clusters was identified. Self-reported heterosexual men were identified as belonging to the pnMSM group if they could be linked to any MSM in their cluster. Multinomial logistic regression was used to determine associated factors of being pnMSM. Results The optimal genetic distance threshold was 0.75% substitutions/site. Among 896 self-reported heterosexual men, the frequency (percentage and 95% confidence interval) was 62 (6.9%, 5.2-8.6%) for pnMSM, 779 (86.9%, 84.7-89.1%) for indeterminate men and 55 (6.1%, 4.5-7.7%) for potential heterosexual men, respectively. Self-reported heterosexual men who were younger, single and more educated were more likely to be pnMSM. Conclusion Based on these findings, there is a need to pay more attention to sexually active, young and educated self-reported heterosexual men and provide them with voluntary counselling and testing and specific HIV prevention services.